Hubungan Indeks Massa Tubuh (IMT) terhadap Daya Tahan Kardiorespirasi pada Pemain Futsal Universitas Bali Internasional - I Komang Arya Triguna; I Made Dhita Prianthara; Komang Tri Adi Suparwati (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Futsal is a high-intensity team sport that requires a combination of speed, agility, and physical endurance, particularly cardiorespiratory endurance. Cardiorespiratory endurance is crucial because it directly relates to a player's ability to maintain optimal performance throughout a match, particularly when facing fast-paced and stressful play. Therefore, variables that can influence this ability, such as body composition and nutritional status, are crucial in developing athlete performance. One indicator that can be used to measure nutritional status and body composition is the Body Mass Index (BMI), which is obtained by measuring weight and height. BMI not only reflects whether a person is within the ideal weight range but also potentially influences the efficiency of the body's organs, including the cardiovascular and respiratory systems. In the context of futsal, players with a higher BMI tend to have a higher body weight, which can hinder movement efficiency and increase fatigue during matches. Conversely, players with a lower BMI may have insufficient energy reserves and muscle mass to maintain stamina during matches. This study shows a significant negative relationship between BMI and cardiorespiratory endurance in futsal players at Bali International University. The results of statistical tests using the Spearman rank correlation method showed a correlation coefficient (r) of -0.504 with a significance value of p = 0.005. This indicates that the higher a player's BMI, the lower their cardiorespiratory endurance tends to be. These findings support the importance of ideal body weight management in futsal athlete training, both through dietary adjustments and measured physical exercise programs.